Analsying The Authority Of Bank Indonesia in Contering The Circulation Of Conterfeit Money - Faqran, Syamsu (Journal Evidence Of Law, 2024)
This research focuses on analyzing the authority of Bank Indonesia in countering counterfeit money circulation. The main issues that become the focus of the study are the counterfeit money circulation efforts undertaken by Bank Indonesia, and the obstacles encountered by Bank Indonesia in counterfeit money circulation. The type of research uses empirical juridical research methods, where data obtained from various sources including interviews conducted to the representatives of Bank Indonesia of Central Sulawesi as the research location. From the research conducted, it is concluded that the efforts made by Bank Indonesia in Combating the Circulation of Counterfeit Money include through cooperation with the Coordinating Agency for the Eradication of Counterfeit Money (Botasupal); Socialization of Explanation of Prevention and Eradication of Counterfeit Money, When Transacting and After Transacting; Socialization of Explanation of Differences between Real Money and Counterfeit Money; and Socialization of Punishment for Counterfeit Money Dealers in Indonesia. And against the obstacles found by Bank Indonesia representatives of Central Sulawesi that, people are reluctant to report the findings of counterfeit money, that people feel worried about being used as witnesses in cases of criminal acts of counterfeit money circulation, people are worried that Bank Indonesia does not provide reimbursement for counterfeit money that was accidentally obtained and the community, especially traders are less careful in receiving money from buyers, as well as information on counterfeit money circulation received by Bank Indonesia is still passive, ie waiting for reports from the public.